2018
DOI: 10.1002/jbt.22237
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Knockdown of SRPX2 inhibits the proliferation, migration, and invasion of prostate cancer cells through the PI3K/Akt/mTOR signaling pathway

Abstract: Sushi repeat‐containing protein X‐linked 2 (SRPX2), a novel chondroitin sulfate proteoglycan, is reported to play a critical role in tumorigenesis. However, the expression and functional role of SRPX2 in prostate cancer have not been defined. Thus, the aim of this study was to investigate the expression and functional role of SRPX2 in human prostate cancer. Our results showed that the expression of SRPX2 was obviously increased in human prostate cancer tissues and cell lines. In addition, knockdown of SRPX2 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Moreover, LIF has been shown to help mediate astrocyte differentiation ( Nakashima et al, 1999 ). The pathogenic role and impact of SRPX2 in GBM ( Tang et al, 2016 ) is less well characterised, despite been well studied in cancer ( Hong et al, 2018 ; Tanaka et al, 2009 ; Lin et al, 2017 ; Zhang et al, 2018 ). Analysis of the pattern of expression of SRPX2 in our dataset found that it was up-regulated in the comparisons between iNSC and iAPC across all patients, and its expression was specifically higher in the GICs of patients 19 and 31 ( Figure 4E ), as expected.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, LIF has been shown to help mediate astrocyte differentiation ( Nakashima et al, 1999 ). The pathogenic role and impact of SRPX2 in GBM ( Tang et al, 2016 ) is less well characterised, despite been well studied in cancer ( Hong et al, 2018 ; Tanaka et al, 2009 ; Lin et al, 2017 ; Zhang et al, 2018 ). Analysis of the pattern of expression of SRPX2 in our dataset found that it was up-regulated in the comparisons between iNSC and iAPC across all patients, and its expression was specifically higher in the GICs of patients 19 and 31 ( Figure 4E ), as expected.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed SRPX2 to play an important role in cancer development and progression. In colorectal cancer, the overexpression of SRPX2 may promote invasiveness of tumor cells [33], and in prostate cancer, a knockdown of SRPX2 affected the proliferation, migration and invasion of cancer cells by partially suppressing the PI3K/Akt/mTOR signaling pathway [34]. PI3K/Akt/mTOR regulates cell proliferation and survival in different cancer types and is usually activated in advanced prostate cancer [35, 36].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been shown to help mediate astrocyte differentiation 72 . The pathogenic role and impact of SRPX2 in GBM 73 is less well characterised, despite been well studied in cancer [74][75][76][77] . Analysis of the pattern of expression of SRPX2 in our data set found that it was up-regulated in the comparisons between iNSC and iAPC across all patients, and its expression was specifically higher in the GICs of patients 19, 31 and 44 (Figure 4 E), as expected.…”
Section: Increased Invasion In Xenografts Derived From Bias/enriched ...mentioning
confidence: 99%